Evaluating the quality of accounting education in the Accounting Department at Sayyed Muhammad bin Ali Al-Senussi Islamic University, a field study from the students’ point of view (Economic studies journal, 2020)
This study aimed to assess the quality of accounting education in the Accounting Department of Sayyid Muhammad bin Ali Al-Senussi Islamic University from the students' point of view. In order to achieve the objectives of the study, a questionnaire was designed and distributed to the study sample, where (31) questionnaires were distributed, (31) valid questionnaires were returned, which represents (100%) of the distributed questionnaires. The study used the statistical program (SPSS) to carry out the necessary tests to ensure the relevance of the study data to the statistical analysis and to evaluate the study hypotheses. Including a one-sample T-Test. After analyzing the study data, the results showed that there is a statistically significant level for the quality of accounting education, and that the axis of the evaluation and examination system is most important to the quality of accounting education in the Accounting Department of the University of Sayyid Muhammad bin Ali Al-Senussi Islamic University from the viewpoint of students. In the light of the mentioned results, the study recommended the necessity of providing transportation services for students to and from the university, and that professors in the accounting department should emphasize the need for students to seek external scientific sources in the field of accounting (university library, internet) in addition to focusing on the need to enter materials or New topics in the accounting department, according to what arises from problems in practice. And taking into account sufficient time when setting the exam schedule so that it is suitable for most students. The responsible authorities should establish public and specialized libraries in the field of economic sciences in general and in the field of accounting in particular in Al-Bayda.
Keywords: accounting education, quality of accounting education, accounting, of Sayyid Muhammad bin Ali Al- Senussi Islamic University